The Differences of Nurses’ Work Stress in The Intensive Care Unit and Inpatient Room in A Psychiatric Hospital - Irman Somantri; Taty Hernawaty; Ratna Multisari (Journal of Nursing Care, 2019)
Inpatient room in a psychiatric hospital is divided into the acute (intensive) room and non-acute (inpatient) room. Several types of research showed different levels of work stress experienced by nurses in those rooms. The work stress is a form of individual response towards physical and psychological demand caused by the interaction of an individual to the working environment. This research aimed to know the difference in the work stress levels of nurses in psychiatric intensive care unit and inpatient room at a Psychiatric Hospital in West Java Province. This research used a comparative analytical design. The 104 samples were chosen through proportional random sampling technique. The data were collected through New Brief Job Stress Questionnaire (New BJSQ) instrument containing 29 items. The technique of data analysis used was the Mann-Whitney test. The results showed that job stress levels of nurses in psychiatric intensive care unit and inpatient room were low with the median score 42 (SD=7.706 for the intensive care unit and in the inpatient room was 38 (SD=6.167). The results of the Mann-Whitney test found p-value (0.047) < 0,.5. In conclusion, there is a bit different in the job stress level of nurses in psychiatric intensive care unit and inpatient room. Maintaining the mechanism of adaptive coping, adding the number of nurses, and the policy regarding nurse room rotation schedules would be solutions to overcome with work stress.